2015
DOI: 10.1016/j.cageo.2015.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Error in target-based georeferencing and registration in terrestrial laser scanning

Abstract: Terrestrial laser scanning (TLS) has been used widely for various applications, such as measurement of movement caused by natural hazards and Earth surface processes. In TLS surveying, registration and georeferencing are two essential steps, and their accuracy often determines the usefulness of TLS surveys. So far, evaluation of registration and georeferencing errors has been based on statistics obtained from the data processing software provided by scanner manufacturers. This paper demonstrates that these sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 26 publications
2
42
0
Order By: Relevance
“…The registration error resulting from the registration of scans from different scan positions and from the multi‐temporal registration is not spatially uniform and can vary significantly between the central parts of the data set and surfaces deviating from the main slope direction. The calculation of the LOD could be further improved by the estimation of a spatially distributed registration error as proposed by Fan et al (), although this is difficult in this case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The registration error resulting from the registration of scans from different scan positions and from the multi‐temporal registration is not spatially uniform and can vary significantly between the central parts of the data set and surfaces deviating from the main slope direction. The calculation of the LOD could be further improved by the estimation of a spatially distributed registration error as proposed by Fan et al (), although this is difficult in this case.…”
Section: Discussionmentioning
confidence: 99%
“…An assessment of the spatial distribution of the registration error is hardly possible because the registration error cannot be distinguished from the positional uncertainties and the surface roughness. The assessment of the registration error by using the error statistics describing how well target constraints are matched (Oppikofer et al , ; Barnhart and Crosby, ; Lague et al ) has been shown by Fan et al () to be an incompetent measure, especially at larger ranges. However, these error statistics are often used for the estimation of the registration error and for uncertainty analyses.…”
Section: Methodsmentioning
confidence: 99%
“…However, the density and arrangement of targets will affect this assessment and, moreover, this method presumes that the target center can be identified exactly by the scanner, which is not always guaranteed (Fan et al, 2015;Fey and Wichmann, 2017). However, it is challenging to estimate registration error because it is difficult to distinguish error associated with the mismatch of points between the two point clouds from scanning noise, which is a property of individual scans.…”
Section: Registration Errormentioning
confidence: 99%
“…An overview of the evolution of soil surface roughness can be found in Li et al (2019). Although limitations of using a single registration error to calculate LOD are recognized (Fey and Wichmann, 2017), the compromise is used routinely because there are no favorable alternatives (Fan et al, 2015). Fey and Wichmann (2017) already found that greater surface roughness resulted in a greater LOD, while lesser surface roughness had a smaller LOD.…”
Section: Level Of Detectionmentioning
confidence: 99%
See 1 more Smart Citation